2019
DOI: 10.1044/2019_jslhr-s-19-0144
|View full text |Cite
|
Sign up to set email alerts
|

Categorical and Dimensional Ratings of Emotional Speech: Behavioral Findings From the Morgan Emotional Speech Set

Abstract: Purpose Emotion classification for auditory stimuli typically employs 1 of 2 approaches (discrete categories or emotional dimensions). This work presents a new emotional speech set, compares these 2 classification methods for emotional speech stimuli, and emphasizes the need to consider the entire communication model (i.e., the talker, message, and listener) when studying auditory emotion portrayal and perception. Method Emotional speech from male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…One potential explanation is that participant gender confounds ratings of unpleasant stimuli; Picou (2016) did not control for gender between participant groups, with more females in the groups with normal hearing and more males in the group with hearing loss. Some investigators have found effects of gender on ratings of valence where females provide lower ratings of valence of unpleasant stimuli than did males (e.g., Grossman & Wood, 1993 ; Natale et al, 1983 ; Vrana & Rollock, 2002 ), although others have not confirmed this effect (e.g., Morgan, 2019 ). Specific to the IADS stimuli, effects of gender on ratings of valence have also been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that participant gender confounds ratings of unpleasant stimuli; Picou (2016) did not control for gender between participant groups, with more females in the groups with normal hearing and more males in the group with hearing loss. Some investigators have found effects of gender on ratings of valence where females provide lower ratings of valence of unpleasant stimuli than did males (e.g., Grossman & Wood, 1993 ; Natale et al, 1983 ; Vrana & Rollock, 2002 ), although others have not confirmed this effect (e.g., Morgan, 2019 ). Specific to the IADS stimuli, effects of gender on ratings of valence have also been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli • Speech materials came from the MESS (Morgan 2019). The full set contains 1800 stimuli recorded by six talkers (3 male, 3 female) in four emotional speaking styles (Angry, Calm, Happy, and Sad).…”
Section: Methodsmentioning
confidence: 99%
“…To create these subsets of stimuli, all of the sentences from the female talkers in the MESS were sorted by their emotion recognition scores from a validation task (Morgan 2019), and the stimuli from each emotion category with the highest recognition rates were equally divided into nine sets. Pilot testing confirmed that these sets of 40 stimuli (10 stimuli × 4 emotions) from the MESS that had similar emotion recognition scores in quiet.…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple models out there for multi-dimensional representation of emotion such as the big five personality theory also known as the five-factor model proposed in [40]which classifies emotion into extroversion, agreeableness, neuroticism, conscientiousness, and openness to new experiences. Morgan [41]proposed the multi-dimensional representation for emotions which are calm, happy, sad, and angry. Two of the proposed dimensions were Activation level and pleasantness level.…”
Section: Emotion Representationmentioning
confidence: 99%
“…Two of the proposed dimensions were Activation level and pleasantness level. But these representations proposed in [41]are limited to only four emotions. Mancini [42]provided a more diverse classification of emotions into valence and arousal, and we decided to proceed with those values.…”
Section: Emotion Representationmentioning
confidence: 99%